Structural characterisation of the human alpha-lactalbumin molten globule at high temperature. - Ramboarina, S; Redfield, C (2003)
Molten globules are partially folded forms of proteins thought to be general intermediates in protein folding. The 15N-1H HSQC NMR spectrum of the human alpha-lactalbumin (alpha-LA) molten globule at pH 2 and 20 degrees C is characterised by broad lines which make direct study by NMR methods difficult; this broadening arises from conformational fluctuations throughout the protein on a millisecond to microsecond timescale. Here, we find that an increase in temperature to 50 degrees C leads to a dramatic sharpening of peaks in the 15N-1H HSQC spectrum of human alpha-LA at pH 2. Far-UV CD and ANS fluorescence experiments demonstrate that under these conditions human alpha-LA maintains a high degree of helical secondary structure and the exposed hydrophobic surfaces that are characteristic of a molten globule. Analysis of the H(alpha), H(N) and 15N chemical shifts of the human alpha-LA molten globule at 50 degrees C leads to the identification of regions of native-like helix in the alpha-domain and of non-native helical propensity in the beta-domain. The latter may be responsible for the observed overshoot in ellipticity at 222 nm in kinetic refolding experiments.